EBV-induced T-cell responses in EBV-specific and nonspecific cancers - Zhang, Qiuting; Xu, Miao (Frontiers in Immunology, 2023)
Epstein-Barr virus (EBV) is a ubiquitous human tumor virus associated with various malignancies, including B-lymphoma, NK and T-lymphoma, and epithelial carcinoma. It infects B lymphocytes and epithelial cells within the oropharynx and establishes persistent infection in memory B cells. With a balanced virus-host interaction, most individuals carry EBV asymptomatically because of the lifelong surveillance by T cell immunity against EBV. A stable anti-EBV T cell repertoire is maintained in memory at high frequency in the blood throughout persistent EBV infection. Patients with impaired T cell immunity are more likely to develop lifethreatening lymphoproliferative disorders, highlighting the critical role of T cells in achieving the EBV-host balance. Recent studies reveal that the EBV protein, LMP1, triggers robust T-cell responses against multiple tumor-associated antigens (TAAs) in B cells. Additionally, EBV-specific T cells have been identified in EBV-unrelated cancers, raising questions about their role in antitumor immunity. Herein, we summarize T-cell responses in EBV-related cancers, considering latency patterns, host immune status, and factors like human leukocyte antigen (HLA) susceptibility, which may affect immune outcomes. We discuss EBV-induced TAA-specific T cell responses and explore the potential roles of EBV-specific T cell subsets in tumor microenvironments. We also describe T-cell immunotherapy strategies that harness EBV antigens, ranging from EBV-specific T cells to T cell receptor-engineered T cells. Lastly, we discuss the involvement of γδ T-cells in EBV infection and associated diseases, aiming to elucidate the comprehensive interplay between EBV and T-cell immunity.